ANALISIS KELAYAKAN BUKU TEKS BAHASA JAWA KURIKULUM 2013 TINGKAT SMP - Lulut Wahyuningsih; Raheni Suhita; Nugraheni Eko Wardani (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2018)
The purpose of this research was to describe the content feasibility and language feasibility on the seventh grade Javanese text book “Marsudi Basa lan Sastra Jawa”. This study is included in qualitative research where the primary data source was the seventh grade Javanese text book “Marsudi Basa lan Sastra Jawa”. Research technique used in this research was content analysis techniques. Data were analyzed using an interactive analysis: data collection, data reduction, data presentation, verification, and drawing conclusions. Data of content feasibility and language feasibility were analyzed by instrument which is based on the relevant theories and information, and assessment of multiple sources. The validity test of the data used triangulation of research and theory. In triangulation researchers involved two other researchers, namely Yessi Estifalia (YE) and Dwi Ratna (DR). Content Feasibility was reviewed from material suitability, accuracy of the material, and the content of learning materials, while the language feasibility was reviewed from language conformity with the level of learners’ development, communicative, and coherent and unity of ideas. From the analysis it can be concluded that: (a) the content feasibility of the seventh grade Javanese text book “Marsudi Basa lan Sastra Jawa” obtained 85.73% of total average score of 82.3 and a maximum score of 96, (b) the language feasibility the seventh grade Javanese text book “Marsudi Basa lan Sastra Jawa” obtained 82.85% of total average score of 23.2 and a maximum score of 28, which still contained 72 mistakes such as spelling, diction, words, and sentences used.